2017
DOI: 10.1002/slct.201601340
|View full text |Cite
|
Sign up to set email alerts
|

Er(OTf)3 Assisted Efficient Synthesis of 3‐Hydroxynaphthalene‐1, 4‐Dione Derivatives via Pseudo Four‐Component Reactions and Their Biological Evaluation

Abstract: A green, operationally simple and highly efficient one pot fourcomponent approach for the synthesis of 2-hydroxy-3-((5hydroxy-3-methyl-1-phenyl-1H-pyrazol-4-yl)(phenyl)methyl) naphthalene-1,4-dione derivatives has been developed by a domino reaction. Ethyl acetoacetate, aromatic aldehyde, 2hydroxynaphthaquinoline and phenylhydrazine derivative was used as the reagent and Er(OTf) 3 as the catalyst. This approach offers the advantages of clean and simple methodology, short reaction time, no column purification, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 67 publications
2
8
0
Order By: Relevance
“…These spectra were confirmed the formation of metal complexes successfully using in-situ preparation at room temperature. These spectra were confirmed that the formation of (Anil-Tolu) 4 and [Pd(Anil-Tolu) 4 (H 2 O) 2 ] successfully by in-situ method. Figure 2 shows the FT-IR spectra of (Anil-Tolu) 4 (a) and its metal complexe [Pd(Anil-Tolu) 4 The bands at 2800-3000 cm-1 due to the stretching of ν(C-H) and the band at ~1598 cm-1 due to the stretching vibration of ν(C=C) and the responses of aldehyde ν(C-H) obtained at 1309 cm-1.…”
Section: Scheme 1: In-situ Synthesis Of Schiff Base [Anil-tolu] Ligandsupporting
confidence: 74%
See 2 more Smart Citations
“…These spectra were confirmed the formation of metal complexes successfully using in-situ preparation at room temperature. These spectra were confirmed that the formation of (Anil-Tolu) 4 and [Pd(Anil-Tolu) 4 (H 2 O) 2 ] successfully by in-situ method. Figure 2 shows the FT-IR spectra of (Anil-Tolu) 4 (a) and its metal complexe [Pd(Anil-Tolu) 4 The bands at 2800-3000 cm-1 due to the stretching of ν(C-H) and the band at ~1598 cm-1 due to the stretching vibration of ν(C=C) and the responses of aldehyde ν(C-H) obtained at 1309 cm-1.…”
Section: Scheme 1: In-situ Synthesis Of Schiff Base [Anil-tolu] Ligandsupporting
confidence: 74%
“…These spectra were confirmed that the formation of (Anil-Tolu) 4 and [Pd(Anil-Tolu) 4 (H 2 O) 2 ] successfully by in-situ method. Figure 2 shows the FT-IR spectra of (Anil-Tolu) 4 (a) and its metal complexe [Pd(Anil-Tolu) 4 The bands at 2800-3000 cm-1 due to the stretching of ν(C-H) and the band at ~1598 cm-1 due to the stretching vibration of ν(C=C) and the responses of aldehyde ν(C-H) obtained at 1309 cm-1. Some of the bands of metal complexes are observed at slightly lower region compared with pure ligand, which confirms the metals were coordinated with Schiff base ligand.…”
Section: Scheme 1: In-situ Synthesis Of Schiff Base [Anil-tolu] Ligandsupporting
confidence: 74%
See 1 more Smart Citation
“…A number of processes have been reported for the syntheses which includes 1‐butyl‐3‐methylimidazolium hydroxide . HOAc under microwave irradiation, [Pyrr][HCOO], DABCO, DBU, Er (OTf) 3 , water under MW, [DBU] 2 [EDS], (4‐sulfobutyl)tris(4‐sulfophenyl) phosphonium hydrogen sulfate, Nano‐Fe 3 O 4 /PEG/succinic anhydride, phenylphosphinic acid, p ‐TSA …”
Section: Introductionmentioning
confidence: 99%
“…Recently, the Schiff bases and complexes were significant in various in pharmaceutical and medicinal field. They display a broad range of biological applications such as antitumor, antifungal, antiviral and antibacterial activity [1][2][3][4][5][6][7][8][9] and also these types of complexes having higher steric hindrance nature by introducing the bulkier substituent in its existing molecules. The stabilization of metal complexes by its metal oxidation nature and it gives good solubility for the spectrum analysis [10][11][12].…”
Section: Introductionmentioning
confidence: 99%